2009
DOI: 10.1016/j.pharmthera.2008.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Functional selectivity of EGF family peptide growth factors: Implications for cancer

Abstract: Breast, prostate, pancreatic, colorectal, lung, and head and neck cancers exploit deregulated signaling by ErbB family receptors and their ligands, EOF family peptide growth factors. EGF family members that stimulate the same receptor are able to stimulate divergent biological responses both in cell culture and in vivo. This is analogous to the functional selectivity exhibited by ligands for G-protein coupled receptors. Here we review this literature and propose that this functional selectivity of EGF family m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
261
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(276 citation statements)
references
References 77 publications
(95 reference statements)
10
261
0
5
Order By: Relevance
“…Recruitment Stimulated by Other EGF Receptor LigandsThe EGF receptor is activated by a family of homologous growth factors, including EGF TGF␣, BTC, HB-EGF, AREG, EPG, and EPR (17). To quantify the similarities and differences in the response of cells to stimulation by each of these ligands, the luciferase complementation assay was used to monitor the recruitment of the eight different signaling proteins to the EGF receptor in response to each of these agonist ligands.…”
Section: Generation and Characterization Of Stable Cell Lines-mentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment Stimulated by Other EGF Receptor LigandsThe EGF receptor is activated by a family of homologous growth factors, including EGF TGF␣, BTC, HB-EGF, AREG, EPG, and EPR (17). To quantify the similarities and differences in the response of cells to stimulation by each of these ligands, the luciferase complementation assay was used to monitor the recruitment of the eight different signaling proteins to the EGF receptor in response to each of these agonist ligands.…”
Section: Generation and Characterization Of Stable Cell Lines-mentioning
confidence: 99%
“…The EGF receptor binds seven different agonist ligands, including some of high affinity (EGF, TGF␣, BTC, 6 and HB-EGF) and some of low affinity (AREG, EPG, and EPR) (17). It has been reported that different EGF receptor ligands induce different responses when binding to the same cell line (18 -21).…”
mentioning
confidence: 99%
“…All ErbB receptors contain an extracellular ligand-binding domain, a single pass transmembrane domain, an intracellular tyrosine kinase, and a C-terminal tail (3). The EGF receptor, ErbB3, and ErbB4 are activated through the binding of a family of homologous ligands (4). Unique among the ErbB receptors, ErbB2 has no known ligand (5,6).…”
mentioning
confidence: 99%
“…Присоединение лиганда к субдоменам I и III индуцирует значительные конформационные перестройки во внекле-точном домене рецептора, который переходит в открытое состояние и димеризуется за счет межмолекулярного вза-имодействия одноименных субдоменов II / II и IV / IV [11].…”
Section: основные клеточные сигнальные пути вовлеченные в патогенез unclassified
“…Протяженная делеция внеклеточного домена EGFR vIII (del-7) ведет к независимой от лигандов активации рецептора. К увели-чению аффинности связывания с EGF и TGF и спонтанной димеризации ведут мутации, нарушающие контакт между субдоменами II и IV [11]. Активирующие мутации ERBB1 и ERBB2 в киназном домене вызывают лиганд-независи-мое увеличение сигнальной активности и резистентность к лечению тирозинкиназными ингибиторами [23].…”
Section: основные клеточные сигнальные пути вовлеченные в патогенез unclassified